Can home visits for early child development be implemented with sufficient coverage and quality at scale? Evidence from the SPRING program in India and Pakistan - Hill, Zelee; Zafar, Shamsa; Soremekun, Seyi; Sikander, Siham; Avan, Bilal Iqbal; Roy, Reetabrata; Aziz, Sarmad; Kumar, Divya; Parveen, Nazia; Saleem, Shumaila; Verma, Deepali; Sharma, Kamal Kant; et al. (Frontiers in Nutrition, 2023)
Introduction: There is limited evidence from low and middle-income settings on the effectiveness of early child development interventions at scale. To bridge this knowledge-gap we implemented the SPRING home visiting programme where we tested integrating home visits into an existing government programme (Pakistan) and employing a new cadre of intervention workers (India). We report the findings of the process evaluation which aimed to understand implementation. Methods and materials: We collected quantitative data on training knowledge gain (self-completed pre and post training test), supervision coverage (programme records), visit coverage (caregiver interviews) and visit quality (field supervision checklist and caregiver interviews). We collected qualitative data on acceptability and barriers and facilitators for change through in-depth interviews with mothers (24); focus group discussions with mothers (8), grandmothers (12), and fathers (12) and in-depth interviews or focus group discussions with the community-based agents and their supervisors (13). Results: Implementation was sub-optimal in both settings. In Pakistan issues were low field-supervision coverage and poor visit quality related to issues scheduling supervision, a lack of skill development, high workloads and competing priorities. In India, issues were low visit coverage - in part due to employing new workers and an empowerment approach to visit scheduling. Coaching caregivers to improve their skills was sub-optimal in both sites, and is likely to have contributed to caregiver perceptions that the intervention content was not new and was focused on play activities rather than interaction and responsivity - which was a focus of the coaching. In both sites caregiver time pressures was a key reason for low uptake among families who received visits. Discussion: Programmes need feasible strategies to maximize quality, coverage and supervision including identifying and managing problems through monitoring and feedback loops. Where existing community-based agents are overstretched and systems strengthening is unlikely, alternative implementation strategies should be considered such as group delivery. Core intervention ingredients such as coaching should be prioritized and supported during training and implementation. Given that time and resource constraints were a key barrier for families a greater focus on communication, responsivity and interaction during daily activities could have improved feasibility.